Food Deserts: A Global Crisis in New York City - Segal, Adi (Consilience, 2010)
This paper discusses the global issue of inner city food deserts. These are areas in which healthy and affordable food options are not available. Research has shown that a lack of nutrition leads to further health problems, cognitive gaps, and unpromising trajectories. Here, past research is analyzed and current programs are evaluated. This article focuses on food deserts in New York City, specifically in Harlem. Some field research is also included. Following a detailed review of the situation, practical recommendations are made to alleviate this crisis.